A creative classroom for everyone: An introduction to a small 'c' creativity framework. (June 2020) - Lasky, Dorothea; Yoon, Susan
Highlights: Data shows a relationship between teachers' CAT scores, Small 'c' Creativity Framework scores, and school context. The Small 'c' Creativity Framework is a successful tool for understanding how teachers foster small 'c' creativity. Semi-structured blocks of time are important in fostering small 'c' creativity in classrooms. Teachers' beliefs about creativity do not affect their curricular choices as much as school context does. Abstract: This study presents two case studies of teachers who participated in a large-scale, NSF-funded professional development project. It investigates how teachers' curricular choices affect the amount of student creativity produced in their classrooms. The study demonstrates how creativity is fostered in students through various styles of teacher beliefs and practices. Analysis includes determining Consensual Assessment Technique (CAT) scores for student products and continua scores along a Small 'c' Creativity Framework. The data shows a relationship between teachers' CAT scores, framework scores, and school context. The framework was determined to be a successful tool for understanding the degree to which teachers foster small 'c' creativity. Other themes emerged that could be examined in future studies, including: 1) teachers' allotment of time and small group collaboration; 2) teachers' beliefs about creativity; and 3) school context.